Environmental Efficiency Analysis Of Global Airlines - Yakath Ali, Nurul Syuhadah (2021)
Airline productivity and efficiency have emerged as areas of tremendous interest among academics and industry analysts following the 1978 Airline Deregulation Act in the United States because being productive and efficient is essential for airlines to survive and thrive under continually increasing competitive market pressures. As there is growing corporate social responsibility (CSR) in the airline industry, understanding and improving the environmental impact of airline operations are crucial. However, a limited number of studies have incorporated environmental factors into assessments of airline efficiency. This study intends to partially fill this gap in the existing literature. Therefore, this study's main objective is to evaluate the environmental efficiency of 54 global airlines in 2017. The study applies a double-bootstrap data envelopment analysis (DEA) and integrates the airline industry's undesirable output of carbon emissions. This study also aims to capture five explanatory variables (weight load factor, alliances, geographical region, number of departures, and the ratio of wide-bodied aircraft to total fleet) as determinants to explain the impacts on airline environmental efficiency in the industry. The results confirmed that the bias-corrected (BC) environmental efficiency (EE) scores were highly robust, as the scores were within the lower and upper boundaries. Moreover, British Airways and Lufthansa were the top two environmentally efficient airlines, while Alaska Airlines and Air Moldova were the bottom two